2016
DOI: 10.1111/iwj.12623
|View full text |Cite
|
Sign up to set email alerts
|

Wound management for the 21st century: combining effectiveness and efficiency

Abstract: Treatment of wounds of different aetiologies constitutes a major part of the total health care budget. It is estimated that 1⋅5-2 million people in Europe suffer from acute or chronic wounds. These wounds are managed both in hospitals and in community care. The patients suffering from these wounds report physical, mental and social consequences of their wounds and the care of them. It is often believed that the use of wound dressings per se is the major cost driver in wound management, whereas in fact, nursing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
262
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(325 citation statements)
references
References 26 publications
1
262
0
16
Order By: Relevance
“…They can have a profound deleterious effect on patient quality of life and are common. For example, it is estimated that, at any given time point, 1.5 to 2 million people in Europe have acute or chronic wounds that require medical care . Moreover, several studies have shown that patients with wounds occupy 27% to 50% of acute hospital beds in Europe on any given day and cost the United Kingdom approximately £5 billion annually in 2012/2013: the latter accounted for 3% of all British health care expenditure in 2012/2013 …”
Section: Introductionmentioning
confidence: 99%
“…They can have a profound deleterious effect on patient quality of life and are common. For example, it is estimated that, at any given time point, 1.5 to 2 million people in Europe have acute or chronic wounds that require medical care . Moreover, several studies have shown that patients with wounds occupy 27% to 50% of acute hospital beds in Europe on any given day and cost the United Kingdom approximately £5 billion annually in 2012/2013: the latter accounted for 3% of all British health care expenditure in 2012/2013 …”
Section: Introductionmentioning
confidence: 99%
“…Chronic wounds cause substantial health care costs and decrease the quality of life . This is partially because of the fact that there is a lack of a diagnostic process in public wound care.…”
Section: Introductionmentioning
confidence: 99%
“…Leg oedema is a frequent finding in the elderly population, and the introduction of compression therapy before surgery may be cost‐effective in this regard. The cost of treating complications is usually significantly higher than those of preventive measures, which has been clearly demonstrated in pressure ulcer and wound care studies. Treating complications will cause multiple additional postoperative appointments, increasing treatment costs remarkably.…”
Section: Resultsmentioning
confidence: 99%